The Effect of Technology and Testing Environment on Speech Perception Using Telehealth With Cochlear Implant Recipients. - Goehring, Jenny L.; Hughes, Michelle L.; Baudhuin, Jacquelyn L.; Valente, Daniel L.; McCreery, Ryan W.; Diaz, Gina R.; Sanford, Todd; Harpstera, Roger; Bacon, Sid; Abbas, Paul (Journal of Speech, Language & Hearing Research, 2012)
Purpose: In this study, the authors evaluated the effect of remote system and acoustic environment on speech perception via telehealth with cochlear implant recipients. Method: Speech perception was measured in quiet and in noise. Systems evaluated were Polycom visual concert (PVC) and a hybrid presentation system (HPS). Each system was evaluated in a sound-treated booth and in a quiet office. Results: For speech in quiet, there was a significant effect of environment, with better performance in the sound-treated booth than in the office; there was no effect of system (PVC or HPS). Speech in noise revealed a significant interaction between environment and system. Subjects' performance was poorer for PVC in the office, whereas performance in the sound-treated booth was not significantly different for the two systems. Results from the current study were compared to results for the same group of subjects from an earlier study; these results suggested that poorer performance at remote sites in the previous study was primarily due to environment, not system. Conclusions: Speech perception was best when evaluated in a sound-treated booth. HPS was superior for speech in noise in a reverberant environment. Future research should focus on modifications to non-sound-treated environments for telehealth service delivery in rural areas.